2019
DOI: 10.1111/resp.13631
|View full text |Cite
|
Sign up to set email alerts
|

Advances in non‐invasive positive airway pressure technology

Abstract: Non‐invasive ventilation (NIV) has become the standard of care for patients with a range of respiratory and sleep breathing disorders. Technological advances have enabled the development of several newer modes of automatically adapting NIV suitable for patients with more complex breathing abnormalities that may be difficult to manage effectively with more traditional positive airway pressure therapy. These modes allow for more stable ventilation when fluctuating ventilation requirements occur such as in positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…3 Over the past 15 years, home ventilators have undergone major technical evolutions; however, sometimes they are of undetermined clinical relevance. [6][7][8] Volume-assured pressure support, autotitrating expiratory positive airway pressure (EPAP), inspiratory positive airway pressure (IPAP), pressure support, backup rates, and built-in algorithms profiled for certain pathologies are now standard options on many ventilators. [9][10][11][12][13][14][15] More importantly, built-in software provides important information for monitoring efficacy of NIV (ie, estimation of leaks, tidal volume, residual respiratory events, percentage of cycles triggered and cycled by the ventilator, compliance).…”
mentioning
confidence: 99%
“…3 Over the past 15 years, home ventilators have undergone major technical evolutions; however, sometimes they are of undetermined clinical relevance. [6][7][8] Volume-assured pressure support, autotitrating expiratory positive airway pressure (EPAP), inspiratory positive airway pressure (IPAP), pressure support, backup rates, and built-in algorithms profiled for certain pathologies are now standard options on many ventilators. [9][10][11][12][13][14][15] More importantly, built-in software provides important information for monitoring efficacy of NIV (ie, estimation of leaks, tidal volume, residual respiratory events, percentage of cycles triggered and cycled by the ventilator, compliance).…”
mentioning
confidence: 99%
“…40 Despite this, it is widely known that large degrees of leakage will significantly affect NIV performance, as well as comfort. 41 Large air leaks can significantly reduce the level of delivered intra-alveolar pressure, indeed the response of the PAP machine can be reduced by up to 56% in the presence of a leak of 30 L/min. Smaller air leaks can be compensated for by the ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no studies investigating NIV leakage in a pediatric population; furthermore, the level of clinical “tolerability” of leaks is not well established in home NIV 40 . Despite this, it is widely known that large degrees of leakage will significantly affect NIV performance, as well as comfort 41 . Large air leaks can significantly reduce the level of delivered intra‐alveolar pressure, indeed the response of the PAP machine can be reduced by up to 56% in the presence of a leak of 30 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no studies investigating NIV leakage in a paediatric population; furthermore the level of clinical "tolerabilty" of leaks is not well established in home NIV 33 . Despite this, it is widely known that leakage will significantly effect NIV performance 34 . In this study we identified that there was significantly greater leak in the DS cohort relative to their non-DS counterparts and this is particularly evident in those aged >5yrs.…”
Section: Discussionmentioning
confidence: 99%